Prehospital medicine learning experience for pharmacy residents. Issue 2 (7th November 2022) - Acquisto, Nicole M.; Cushman, Jeremy T.; Johnston, Melinda; Sensenbach, Benjamin
Abstract: Pharmacist collaboration with medical directors and practitioners operating in the emergency medical services (EMS) system can improve overall care, optimize the medication formulary, and decrease medication‐related risk. However, to achieve this, pharmacists must have a fundamental understanding of the prehospital medicine environment. We describe a comprehensive prehospital medicine postgraduate training experience for postgraduate year two (PGY2) emergency medicine (EM) pharmacy residents. A detailed description of the prehospital medicine learning experience (LE) is provided that includes an immersive schedule with diverse EMS exposure, attendance at dedicated EMS‐specific medical resident conferences, didactic and self‐learning requirements, and a scholarly EMS project. Information regarding how this LE is organized and evaluated, as well as challenges and future directions are provided. Program success is highlighted with the reporting of 20 scholarly projects completed by PGY2 EM pharmacy residents from 2006 through 2022 in collaboration with EMS and the Division of Prehospital Medicine. A collaborative and immersive prehospital medicine LE for PGY2 EM pharmacy residents can be mutually beneficial for the training of the pharmacy resident, scholarly productivity supporting regional and statewide change, and EMS personnel.